School Leadership and Management in a Context of Autonomy and Accountability - Cuadrado Muñoz, Francisco J. (Avances en Supervisión Educativa, 2024)
School leadership and management contribute to to the improvement of school achievements and are developed together, almost like two sides of the same coin, in a context of autonomy with accountability, despite the complexity, possibilities and limitations that they may have in their development. This article addresses a review of existing literature on the subject and relevant contributions of interest, and despite the fact that little is known about how schools and school leaders use autonomy in practice to improve quality and equity, there are useful conclusions from different investigations that allow us to establish aspects to consider for the development of successful school management and leadership, in any case compatible with the exercise and practice of autonomy, and its consequent accountability.
Keywords: Leadership; educational management; school autonomy; accountability